PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI TERHADAP KOMITMEN ORGANISASI PADA KARYAWAN PT. BANK BTN CABANG PEKANBARU - Reni Susanti; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of the study is to determine the effect of transformational leadership style and motivation toward organizational commitment of employees of PT. Bank BTN Branch Pekanbaru. Where there are two independent variables are kepemipinan transformational style and motivation and the dependent variable organizational commitment. The population in this study were permanent employees at the Employee PT. BTN Bank Branch Pekanabaru. Sampling the census method as many as 81 people. The research data in the form of primary data and secondary data, with the questionnaire as a research instrument. Analysis of the data used by using SPSS. Results of analysis using multiple linear regression, t-test, test of determination (R2), and F. Test results showed that transformational and motivational style kepemipinan simultaneously significant effect on organizational commitment. this can be seen from the F-count = 52.867 > F-table = 3.11. So that the figures obtained R2 (R Squar) of 0.325 or 32.5%. This shows that the percentage contribution of independent variables (transformational leadership and motivation) on the dependent variable (organizational commitment) of 32.5%. While the remaining percentage of 67.5% (100% -32.5) is influenced by other variables not included in this study variables.Keywords: Transformational Leadership Style, Motivation, Organizational Commitment.